Reduction of Students’ Biological Misconceptions through the Conceptual Change Model Integrated with Android-Based Quran - Hamid, Abdul; Haka, Nukhbatul Bidayati (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2021)
This research aimed to reduce students’ misconceptions using a conceptual change model assisted by the integrated Android-based Quran. The study used a quasi-experimental design with a one-group pretest-posttest design. The study involved 95 eleventh-grade students MAN 1 Bandar Lampung. The research instrument was multiple-choice questions equipped with a certainty of response index (CRI) developed based on the revised Bloom taxonomy indicator. The data collection techniques used were tests (pretest and posttest). The results of the study obtained a reduction value of misconceptions in the pretest, namely understanding the concept of 47 % (moderate), misconception 48 % (moderate), and not understanding the concept of 5 % (low). The posttest score decreased (reduced) the proportion of misconceptions to 42 % (moderate), not understanding the concept to 4 % (low), and understanding the concept to 55 % (moderate). The hypothesis testing employed was the one-sample t-test. Therefore, H1 was accepted. It means that the conceptual change model (MCC) with Android-based Quran media can reduce students’ misconceptions with a criterion of 0.71 (medium interval). Thus, the results of this research can add to the treasury of studies on the reduction of misconceptions through the MCC model based on the Android-based Quran media. Also, as a practical use for teachers to deepen the concept of biology to guide students to understand the concept of the material better correctly.